VARIASI POLA SIDIK JARI PADA MASYARAKAT DESA DAUP KINTAMANI, BANGLI-BALI - Made Nanda Equilla Putri; I Ketut Junitha; Ni Nyoman Wirasiti (Program Studi Biologi Universitas Udayana, 2025)
Daup Village is one of the traditional villages in the Kintamani highlands that still carries out religious rituals, the structure of ancient Balinese society. Daup Village is an expansion or separation from the traditional village of Selelulung. Selulung Village in its history is part of the gebog domas community with the main temple, namely the Panarajon Temple which consists of the gebog satak Sukawan, Kintamani, Batang and Selulung.This study aims to determine the variation of fingerprint patterns and compare ID, IF and the number of male and female community tendrils in Daup Village, Kintamani, Bangli, Bali. In this study as many as 59 Probandus from Daup Village were used consisting of 30 men and 29 women who did not have family relations. The Purposive Sampling Method was used in this study which was conducted in November-December 2023. The results of the fingerprint examination showed that there were six fingerprint patterns on the samples of women and male villages with different frequencies and uneven distributions in the five fingers from both hands. The Dankmeijer Index (ID) for the female group is 19,527, slightly higher than the male group of 18,232. Conversely, the Furuhata Index (IF) for the male group is 210,465, higher than the female group, 192,045.The average number of TRC was 141.86 in males and 150.27 in females in Daup Village, which was not statistically significantly different. Based on fingerprint data Daup and Selulung communities. Are diferent. Kata Kunci: fingerprints, arch, loop, whorl, Indeks Dankmeijer, Indeks Furuhata, Daup Village